2020
DOI: 10.1177/1753425919899132
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells inhibit the differentiation and effector functions of monocytes

Abstract: Although monocytes represent an essential part of the host defence system, their accumulation and prolonged stimulation could be detrimental and may aggravate chronic inflammatory diseases. The present study has explored the less-understood immunomodulatory effects of mesenchymal stem cells on monocyte functions. Isolated purified human monocytes were co-cultured with human umbilical cord-derived mesenchymal stem cells under appropriate culture conditions to assess monocytes’ vital functions. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This is consistent with in vitro data where MSCs support monocyte survival through direct interaction while increasing expression of M2 markers, phagocytic capacity and antiinflammatory cytokines secretion via the production of PGE2 (46). MSCs also inhibit monocyte differentiation into dendritic cells (DC) and macrophages, decrease their phagocytosis functions and block their capacity to stimulate T cell proliferation (47). After phagocytosis of human UC-MSCs by monocytes, phagocytic monocytes acquired a predominantly anti-inflammatory phenotype characterized by increased IL-10 secretion, decreased TNF-a production and expression of M2type receptors such as CD163 and CD206 (48).…”
Section: Mscs and Inflammatory Response: A Question Of Cell Dialoguesupporting
confidence: 89%
“…This is consistent with in vitro data where MSCs support monocyte survival through direct interaction while increasing expression of M2 markers, phagocytic capacity and antiinflammatory cytokines secretion via the production of PGE2 (46). MSCs also inhibit monocyte differentiation into dendritic cells (DC) and macrophages, decrease their phagocytosis functions and block their capacity to stimulate T cell proliferation (47). After phagocytosis of human UC-MSCs by monocytes, phagocytic monocytes acquired a predominantly anti-inflammatory phenotype characterized by increased IL-10 secretion, decreased TNF-a production and expression of M2type receptors such as CD163 and CD206 (48).…”
Section: Mscs and Inflammatory Response: A Question Of Cell Dialoguesupporting
confidence: 89%
“…Maqbool et al showed reduced monocyte differentiation into macrophages and dendritic cells by the presence of MSC. Moreover, either the phagocytic activity or the capability to induce T lymphocyte proliferation of each subgroup of myeloid cells were also blocked by MSCs [116]. On the other hand, the immunomodulatory effect of MSCs on monocytes and dendritic cells has also been reported in rheumatoid arthritis.…”
Section: Mesenchymal Stem Cell Therapy Targeting Osteoclastmentioning
confidence: 96%
“…Anti-inflammatory monocytes secrete high levels of IL-10 but decreased levels of TNF-α, IL-12, IL-1β, and IL-17 [ 39 , 51 , 64 , 65 ] ( Figure 1 ). A recent study showed that MSCs can also suppress monocyte functions [ 66 ] ( Figure 1 ). More precisely, when human MSCs derived from the umbilical cord were cultured with human monocytes, the latter had decreased potential to differentiation into macrophages, defective phagocytic capacity, and antigen-presenting potential.…”
Section: Msc Characteristics and Immunomodulatory Propertiesmentioning
confidence: 99%